Peer-Personality Engagement dalam Upaya Memperkuat Sinerjitas dalam Proses Komunikasi Manajemen - Saudah Saudah (Universitas Merdeka Malang, 2020)
Effective management communication is an important key for the implementation of a work environment that uses telematics equipment. This illustrates the dual conditions that reflect the use of technological devices, as well as contributions made by creative thinkers, thus emphasizing the quality and quantity of dynamizing personal interests into the organization. In conditions carried by routine, there are still many work organizations experiencing a decrease in productivity which is inversely proportional to the strengthening of the family atmosphere among individuals. Conflicts that often arise in the work environment are understood as conditions that are not conducive, but unwittingly becomes one of the steps to return the individual to a proportional position, and this is where it actually is without realizing the importance of peer-personality engagement to overcome organizational problems that are always developing. By using a literacy approach to several research and literature publications, supported by empirical experience in work organizations that use telematics bases, and then verify some information that has been obtained to formulate the results of the study. The results of the study put management communication under very strong pressure to harmonize relationships, and as quickly as possible balance the various interests of the urgent work organization. Strengthening synergy through the management communication process, has put peer-personality engagement as a quality standard to solve organizational problems with the following this statement: (1) agreed as a guideline and habit in every action that leads to improving the quality of work organization; (2) making it a measure of determining the level of risk to be received by comparing costs and rewards; and (3) determine and socialize these two things as rules or values that are always negotiated so that they can be improved according to circumstances. Keywords: Peer-Personality Engagement, Work Environment, Management CommunicationDOI: https://doi.org/10.26905/nomosleca.v6i1.4038